News media socialisation and ethnic tolerance among Malaysian youth - Tamam, Ezhar; Yee, Wendy Mei Tien; Idris, Fazilah; Hamzah, Azimi (Universiti Putra Malaysia Press, 2008)
Youth which make up a substantial portion of the Malaysian multiethnic population are increasing confronted with contentious interethnic relations issues. Hence, it is very pertinent to ask their level of ethnic tolerance. Strengthening ethnic tolerance among the youth involves educating them with the cultural differences and issues of interethnic relations through the mainstream news media. The fact that the youth are heavy consumer of media and the news media are important sources of information, it is also imperative to know the level of exposure and attention to news of public affairs among the youth. Drawing on the media effect assumption, it is predicted that exposure and attention to public affairs news in the mainstream news media would sensitize the youth to the complexity and challenges of living in a multiethnic, multicultural society and accordingly enhance their level of ethnic tolerance. But the relationship of exposure to public affair news in the local news media and ethnic tolerance has not been adequately studied.